Knockdown of Human TCF4 Affects Multiple Signaling Pathways Involved in Cell Survival, Epithelial to Mesenchymal Transition and Neuronal Differentiation - Forrest, Marc P.; Waite, Adrian J.; Martin-Rendon, Enca; Blake, Derek J. (PLOS ONE, 2013)
Haploinsufficiency of TCF4 causes Pitt-Hopkins syndrome (PTHS): a severe form of mental retardation with phenotypic similarities to Angelman, Mowat-Wilson and Rett syndromes. Genome-wide association studies have also found that common variants in TCF4 are associated with an increased risk of schizophrenia. Although TCF4 is transcription factor, little is known about TCF4-regulated processes in the brain. In this study we used genome-wide expression profiling to determine the effects of acute TCF4 knockdown on gene expression in SH-SY5Y neuroblastoma cells. We identified 1204 gene expression changes (494 upregulated, 710 downregulated) in TCF4 knockdown cells. Pathway and enrichment analysis on the differentially expressed genes in TCF4-knockdown cells identified an over-representation of genes involved in TGF-β signaling, epithelial to mesenchymal transition (EMT) and apoptosis. Among the most significantly differentially expressed genes were the EMT regulators, SNAI2 and DEC1 and the proneural genes, NEUROG2 and ASCL1. Altered expression of several mental retardation genes such as UBE3A (Angelman Syndrome), ZEB2 (Mowat-Wilson Syndrome) and MEF2C was also found in TCF4-depleted cells. These data suggest that TCF4 regulates a number of convergent signaling pathways involved in cell differentiation and survival in addition to a subset of clinically important mental retardation genes.